Évergétisme et sol public en Hispanie sous l’Empire - Bertrand Goffaux (Mélanges de la Casa de Velázquez, 2003)
This paper deals with the status of grounds where public constructions were built in Hispanic cities, taking as a starting point an inscription from Obulco (CIL, II2/7, 97) that includes the formula solo empto ab re publica. This formula, it is argued, indicates that the ground was bought from the community by the benefactor, and not that the city purchased it from a third party. This reading highlights the pragmatism of municipal authorities and sheds new light on the quid pro quo relationship between the cities and their benefactors.